2017
DOI: 10.1186/s40463-017-0225-z
|View full text |Cite
|
Sign up to set email alerts
|

The palisade cartilage tympanoplasty technique: A systematic review and meta-analysis

Abstract: BackgroundTympanoplasty is a common procedure performed by Otolaryngologists. Many types of autologous grafts have been used with variations of techniques with varying results. This is the first systematic review of the literature and meta-analysis with the aim to evaluate the effectiveness of one of the techniques which is gaining popularity, the palisade cartilage tympanoplasty. PubMed, EMBASE, and Cochrane databases were searched for "palisade", “cartilage”, “tympanoplasty”, "perforation" and their synonyms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
1
16
0
2
Order By: Relevance
“…In the systematic review and meta-analysis by Jeffery et al, they found that Palisade Cartilage Tympanoplasty has an overall take rate of 96% at beyond 6 months and has similar odds of complications compared to temporalis fascia. The air-bone gap closure is statistically similar to the reported results from temporalis fascia tympanoplasty [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…In the systematic review and meta-analysis by Jeffery et al, they found that Palisade Cartilage Tympanoplasty has an overall take rate of 96% at beyond 6 months and has similar odds of complications compared to temporalis fascia. The air-bone gap closure is statistically similar to the reported results from temporalis fascia tympanoplasty [ 24 ].…”
Section: Discussionsupporting
confidence: 84%
“…There are several techniques reported in the literature for cartilage myringoplasty including the cartilage-perichondrium composite graft, butterfly techniques, palisade cartilage tympanoplasty, and diced cartilage. 4 We used the cartilage-perichondrium graft technique in this study to maximize the graft acceptance rate by preventing the risk of mobilization of the graft.…”
Section: Discussionmentioning
confidence: 99%
“…In the meta-analysis conducted by Jeffery et al, the palisade cartilage tympanoplasty was found to have an overall 96% success rate with similar ABG closure level to temporalis fascia tympanoplasty. 4 Mohanty et al compared the clinical outcomes of endoscopic cartilage versus temporalis fascia grafting in anterior quadrant perforations and they reported an overall success rate as 91.9% in cartilage and 79% in fascia groups. The changes in ABG were similar in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…1 Various techniques of cartilage tympanoplasty have been proposed. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] We use an over-under technique, where the cartilage-perichondrial island graft is placed lateral to the malleus and medial to the annulus. We also use a cartilage shim between the native tympanic membrane and the cartilage graft when the graft does not make contact with the tympanic membrane, and we believe this additional step is unique.…”
Section: Introductionmentioning
confidence: 99%